Are mobile phones predominant in dual-frame computer assisted telephone interviewing surveys? - Vicente, Paula (International journal of market research, 2025)
The effectiveness of Computer Assisted Telephone Interviewing (CATI) surveys relying on fixed telephone numbers has been eroded by the rise in mobile phone usage and the growing population reachable exclusively through mobile phones. As a result, telephone survey methodologists have had to come up with research designs capable of dealing with the coverage bias in CATI surveys caused by incomplete fixed phone directories. The methodological and operational issues of dual-frame surveys, namely those combining fixed phones and mobile phones, have been extensively investigated, but a comprehensive overview of the magnitude of mobile phone use in CATI surveys is lacking. The present study explores this research gap by analysing data from 675 CATI surveys conducted in European countries. Although a generalised scenario of single frame mobile phone designs is not yet visible, the predominance of mobile phone units over fixed phone units in dual-frame CATI surveys is evident. The sampling method and the target population are the survey-related features most strongly associated to the percentage of mobile phone units in the sample. Survey organisations in countries which continue to have a high number of fixed phone subscriptions tend to give less weight to mobile phone frames in their dual-frame designs.